Use of jet ventilation in thoracoscopic tracheo‐esophageal fistula repair—can both surgeons and anesthesiologists be happy?. Issue 8 (30th March 2015) - Ehlers, Melissa; Pezzano, Chad; Leduc, Laura; Brooks, John; Silva, Plinio; Oechsner, Helena; Crnkovic, Anica; Galay, Igor; Afroze, Farzana; Polaner, David
Summary Laparoscopic and open thoracic surgery in the neonate typically results in hypercapnea and low cardiac output with often poor surgical visualization as the anesthesiologist attempts to correct the respiratory derangements usually seen. We describe three cases in which jet ventilation provided not only superior ventilation with a return to normocapnea but also ideal operating conditions. In addition, jet ventilation utilizes lower mean airway pressures which typically results in improved cardiac output.